Combustion of Pure, Hydrolyzed and Methyl Ester Formed of Jatropha Curcas Lin oil - Muhaji, Muhaji; Wardana, I.N.G; Yulianti, Y; Nursasongko, M (International Journal of Renewable Energy Development, 2015)
The density and viscosity of vegetable oil are higher than that of diesel oil. Thus its direct combustion in the diesel engine results many problems. This research was conducted to investigate the flame characteristics of combustion of jatropha curcas lin in pure, hydrolyzed and methyl ester form. The results indicated that the combustion of pure jatropha curcas lin occurs in three stages, hydrolyzed in two stages    and methyl ester in one stage. For pure jatropha curcas lin, in the first stage, unsaturated fatty acid burned for  0.265 s.  It is followed by saturated fatty acid, burned for 0.389 s in the second stage. And, in the last stage is the burned of glycerol for 0.560 s. Meanwhile for hydrolyzed one, in the first stage, unsaturated fatty acid burned for 0.736 s, followed by saturated fatty acid, burned  for 0.326 s in the second stage. And the last, for methyl ester is the burned for 0.712 s. The highest burning rate was for methyl ester which was 0.003931cc/s. The energy releasing rate of methyl ester, which was for 13,628.67 kcal/(kg.s) resembled that of diesel oil the most, while the lowest rate was for pure jatropha curcas lin which was 8,200.94 kcal/(kg.s). In addition, massive explosion occurred in the fuel containing unsaturated fatty acid and glycerol